Contribution to the Knowledge of Upper Cretaceous Beds in Kočevje and Gorski Kotar Area (NW Dinarides) - Pleničar, Mario; Dozet, Stevo (Geologija, 1993)
On the basis of the characteristic fossil associations biostratigraphic subdivision has been carried out in continuously deposited Upper Cretaceous sedimentary succession of the Kočevje and Gorski Kotar area. Relying on macropaleontologic data it has been possible to define almost all assemblage zones being used for biozonation of the Upper Cretaceous deposits in Outer Dinarides.